Comparing the Effects of Rosemary Ointment and Ginger Ointment on Pain and Physical Performance of Elderly People With Knee Osteoarthritis: A Randomized Controlled Clinical Trial - Ehsan Asadi; Mohammad Gholami; Razieh Shirzadegan; Yaser Mokhayeri; Afsaneh Beiranvand (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Local treatment for knee osteoarthritis (KO) is used to relieve pain, maintain or improve joint function, and reduce disability and patient dependence. This study aims to compare the effect of rosemary ointment and ginger ointment on pain and physical performance of elderly people with KO. Methods & Materials This is an open-label randomized controlled clinical trial. The study population consists of older adults with grade 1 or KO referred to a orthopedic clinic in Lorestan, Iran. Of these, 111 eligible elderly patients were selected and randomly divided into two intervention groups of ginger (n=37), and rosemary (n=37) and one control group (n=37). The intervention groups used ginger or rosemary ointments twice in the morning and evening for 14 days. The control group received standard drug treatments (ibuprofen). The pain and physical function of the elderly before and after the intervention were evaluated using the visual analogue scale and the WOMAC index, respectively. Data analysis was done using paired t-test, analysis of covariance and Tukey's test. Results There was a significant difference in pain intensity and physical performance before and after the intervention in the intervention groups (P<0.001). A significant difference was observed in pain intensity and physical performance after the intervention between the intervention and control groups (P<0.001), but the difference between the two intervention groups was not significant (P>0.05). Conclusion Both ginger and rosemary ointments can improve physical performance and reduce pain in the elderly with KO.